A Short History of Charleston - Rosen, Robert N., 1947- (Book collections on Project MUSE., 2021)
"Beginning with the founding of colonial Charles Town and ending three hundred and fifty years later in the present day, Robert N. Rosen's fast-paced narrative takes the reader on a journey through the city's complicated history as a port to English settlers, a metropolis built on slave labor, a bloodstained battlefield, and a picturesque vacation mecca. Packed with anecdotes and enlivened by passages from diaries and letters, A Short History of Charleston recounts in vivid detail the port city's development from an outpost of the British Empire to a bustling, modern city. This revised and expanded edition includes a new final chapter that discusses the consequential decades that spanned Joseph Riley's forty years as mayor (1975-2016). Rosen traces the city's rapid growth, in geographic size, overall population, and cultural importance. He also contemplates the city's triumphs and its challenges, allowing readers to consider how Charleston's past has shaped its present and will continue to shape its future"--